2015
DOI: 10.1159/000381629
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Monitoring in Lean, Obese and Diabetic Children and Adolescents

Abstract: Aim: To determine if children and adolescents who have obesity (Ob) or type 2 diabetes (T2DM) of relatively short duration have impaired cardiovascular function compared with lean subjects using 24-hour ambulatory blood pressure as a surrogate measure of evaluation. Methods: We enrolled 100 African-Caribbean subjects (45 males/55 females), mean ages 14.4-15.2 years (range 11.8-18.5 years) and Tanner stage 4.2-4.8. Mean BMI for the Ob (n = 40), T2DM (n = 39) and lean (n = 21) groups were 40.3, 34.2 and 20.8, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
3
3
1
Order By: Relevance
“…The 24-hours nocturnal SBP reduction was significantly lower in obese subjects compared to controls. This finding is in agreement with the results published by Shikha [23]. For the mean nocturnal DBP reduction the difference was not significant as it was observed in the above mentioned study [23].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The 24-hours nocturnal SBP reduction was significantly lower in obese subjects compared to controls. This finding is in agreement with the results published by Shikha [23]. For the mean nocturnal DBP reduction the difference was not significant as it was observed in the above mentioned study [23].…”
Section: Discussionsupporting
confidence: 93%
“…The nocturnal systolic dip decreased significantly in the obese children compared to controls; finding that is conflicting with the results of Shikha et al [23].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The mean systolic and diastolic blood pressures of the overweight/obese group were also higher compared to the lean group. This was congruent to the study of Shikha et al, 34 that daytime, nocturnal and 24-hour mean systolic blood pressure were significantly higher in obese subjects. Obesity is known as a major risk for hypertension because it surges tubular reabsorption impairing pressure natriuresis resulting to volume expansion thru the activation of the renin-angiotensin system.…”
Section: Discussionsupporting
confidence: 92%
“…A few studies using ABP monitoring have shown a positive correlation between systolic BP and increased LVMI [ 13 15 , 20 ]. However, these studies either did not evaluate the independent effect of obesity [ 20 ], or were conducted on biased populations (children with casual hypertension [ 13 ], at risk for hypertension [ 14 ], or with other complications [ 15 ]). To our knowledge, no study has comprehensively investigated the relationship between obesity, ABP and measures of cardiac remodeling in otherwise healthy children.…”
Section: Introductionmentioning
confidence: 99%